Anatomi Kurikulum Pendidikan Agama Islam di Sekolah - Marliana, Marliana (Dinamika Ilmu: Jurnal Pendidikan, 2013)
Anatomy of curriculum is described as the components that must be present in every curriculum that can be used for the learning process. They are objectives of the curriculum, materials of teaching, contents of the curriculum, strategies or methods, media and evaluation and improvement of teaching. These components are interconnected to one another. Each component has a content which is very important for the continuity of the curriculum. One of the most important parts of the curriculum is procces of learning as an empowering or enable the students. Thus, the need for active and participatory interaction between students and academic material or with a certain situation so that matter can be transformed into the learning experience of students.